Pengaruh Risiko Likuiditas, Risiko Kredit, Risiko Operasional, Pertumbuhan Aset, dan Margin Bunga Bersih terhadap Kinerja Keuangan - Nurfiah, Nurfiah; Novera Kristianti Maharani (Universitas Sains dan Teknologi Komputer, 2025)
The study was conducted as an analysis of the impact of liquidity risk, credit risk, operational risk, asset growth, and net interest margin on financial performance. This study consists of five independent variables consisting of liquidity risk with a proxy for the Loan to Deposit Ratio, credit risk proxied by NonPerforming Loan, operational risk proxied by Operating Expenses to Operating Income, Asset Growth proxied by the Asset Growth Ratio, Net Interest Margin as a measure of net interest margin, and financial performance measured by Return on Assets. There are 39 banks with a total of 117 observation data samples in the study. With the object of research conventional banks that report their annual reports on the IDX in 2021-2023. Based on the results of the study, liquidity risk and asset growth do not affect financial performance. Credit risk and operational risk have a negative effect on financial performance. Also, the net interest margin has a positive effect on financial performance.